Characterization and compressive property of Mg alloy-ceramic sphere composites. (20th August 2018) - Liu, H M; Sun, C; Liu, J A; Lu, Y
Abstract: Magnesium matrix composites reinforced with Al2 O3 ceramic sphere (i.e., AZ91D-Al2 O3 sphere composites) were prepared by infiltration casting method. The morphology, microstructure, elements, phase compositions of the composites were observed by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and x-ray diffraction (XRD), respectively. And the compressive properties at room temperature and elevated temperatures were investigated. The experimental results show that the ceramic spheres are uniformly distributed in the AZ91D matrix alloy. The surface of the ceramic sphere provides a site for heterogeneous nucleation of Mg17 Al12 phase. The compressive strengths of the composites and AZ91D alloy are reduced with the increase of temperature. However, the composites show the higher compressive strength than the AZ91D alloy at evaluated temperatures. The deformation behaviors were observed and the failure mechanisms at room temperature and elevated temperatures were discussed.